Gastro-Intestinal Parasites of Red Panda (Ailurus Fulgens Fulgens Cuvier, 1825) in Rara National Park, Mugu, Nepal - Shrestha, Chandra Kajipan; Maharjan, Mahendra (Journal of Natural History Museum, 2018)
A total of 22 faecal samples of Red panda were collected in the month of May/June 2011 and 21 faecal samples from the same site during the month of May/June 2012. All the samples were microscopically examined by faecal floatation and sedimentation techniques. Out of 43 faecal samples, 40 samples (93.02%) were found positive for gastro-intestinal parasites. Altogether, 12 different species of gastro-intestinal parasites were recovered from Red panda. Among them, two species of protozoan parasites and 10 species of helminthes were observed. In protozoan parasites, Eimeria (67.44%) was more prevalent as compared to Entamoeba (62.79%). Among helminthes, Oxyuris sp. showed the highest prevalence rate followed by Toxoascaris sp. (48.84%), Hookworm (44.19%), Baylisascaris sp., Crenosoma sp. (34.88%), Strongyloides sp., Moniezia sp. (18.60%), Trichuris sp., etastrongylus sp. (4.65%) and Angiostrongylus sp. (2.33%). Only one species of cestoda i.e. Moniezia sp. was found but trematodes and acanthocephalans were not found in Red Panda of Rara National Park. J. Nat. Hist. Mus. Vol. 29, 2015, Page: 78-90